Using the Analytic Network Process to evaluate the relation between Reverse Logistics and corporate performance in Brazilian companies - Hernández, Cecilia Toledo [UNESP]; Castro, Roberto Cespón; Marins, Fernando Augusto Silva [UNESP]; Durán, Jorge Alberto Rodríguez (My University, 2012)
Reverse Logistics activities are practiced by most Brazilian companies. However, a relevant problem is to identify how different Reverse Logistics programs can affect corporate performance indicators. Analytic Network Process is one of the analytical tools, which can be used to handle a multi-criteria decision-making problem and it is the only one that can capture the interdependencies between the criteria under consideration. This method was adopted here to study the influence of Reverse Logistics practices in corporate performance. Preliminary results indicated that the method can be used, reaching a result compatible to the reality of the Brazilian companies.
Keywords: Analytic Hierarchy Process (AHP); Analytic Network Process (ANP); Reverse Logistics